"He just smiled and gave me a Vegemite sandwich": Advertising Australia's national food in the United States, 1968-1988. (15th August 2016) - Contois, Emily J.H.
Abstract : Purpose: Through a case study of J. Walter Thompson and Kraft's efforts to market Vegemite in the USA in the late 1960s, this paper aims to explore transnational systems of cultural production and consumption, the US's changing perception of Australia and the influence of culture on whether advertising fails or succeeds. Design/methodology/approach: This paper draws from archival primary sources, including advertisements and newspapers, as well as secondary literatures from the fields of advertising history, food studies and transnational studies of popular culture. Findings: Although J. Walter Thompson's advertising contributed to Vegemite's icon status in Australia, it failed to capture the American market in the late 1960s. In the 1980s, however, Vegemite did capture American interest when it was central to a wave of Australian popular culture that included films, sport and music, particularly Men at Work's hit song, " Down Under ", whose lyrics mentioned Vegemite. As such, Vegemite's moment of success stateside occurred without a national advertising campaign. Even when popular, however, Americans failed to like Vegemite's taste, confirming it as a uniquely culturally specific product. Originality/value: This paper analyzes a little-studied advertising campaign. The case study's interdisciplinary findings will be of interest to scholars of advertising history, twentieth century USA and Australian history and food studies.